Measuring Community Resilience using Online Toolkits - Paul Monaghan; Emily Ott; Timothy Fogarty (EDIS)
When we return to the scene of recent disasters like New Orleans, we find that some communities and neighborhoods are able to recover faster than others, while some never completely recover. Community Resilience is defined as the ability for a community to bounce back from a disaster, adapt to changes, and become more sustainable. The resilience assessment and planning tools reviewed here range from simple, ready-to-print worksheets intended for use by average citizens to comprehensive planning exercises more appropriate for city planners, emergency service providers, and elected officials. Not all of the toolkits will apply to every community. This 6-page fact sheet was written by Paul Monaghan, Emily Ott, and Timothy Fogarty, and published by the UF Department of Agricultural Education and Communication, July 2014. (UF/IFAS photo by Tyler Jones)